Effect of soft-tissue impingement on range of motion during posterior approach Total Hip Arthroplasty: an in vivo measurement study. Issue 1 (1st January 2016) - Nakamura, Nobuo; Maeda, Yuki; Hamawaki, Makoto; Sakai, Takashi; Sugano, Nobuhiko
Abstract: Purpose: While implant impingement and bony impingement have been recognized as causes of poor outcomes in total hip arthroplasty (THA), reports of soft-tissue impingement are rare. To clarify the issue, the effect of anterior capsule resection on hip range of motion (ROM) was quantitatively measured in vivo during posterior approach THA using a CT-based hip navigation system. Materials and methods: For 47 patients (51 hips), hip ROM was measured intraoperatively before and after resection of the anterior hip capsule, and the difference was compared. Results: Resection of the anterior hip capsule brought about an average 6° increase of ROM in the direction of flexion with internal rotation and did not markedly change ROM in other directions. Conclusions: During THA through a posterior approach, soft-tissue impingement by the anterior hip capsule can occur. Clinically, we expect that resection of the anterior hip capsule can reduce the risk of posterior instability without increasing the risk of anterior instability.